Modification of Soybean Skin Peeler With Blower - Lestari Andaluri; Achwil Putra Munir; Sulastri Panggabean (Universitas Sumatera Utara, 2015)
In general, soybean epidermis peeler bring out soybean seeds along with the epidermis so it must be separated manually. Improvement is necessary to solve the problem. One of the alternatives is to modify the peeler by adding blower. With the addition of the blower, the soybean seeds and the epidermis brought out separately so that the peeler work capacity can be improved. Soybean epidermis peeler with blower was designed to peel the epidermis in the dry state. Blower in this peeler was centrifugal blower with 150 Watts of power, 3000 rpms of speed, and 2 inches diameter of the output hole. Effective capacity of the modified soybean epidermis peeler with blower in this study was divided into three different rate was blower with maximum rate was 54,64 kg/h; blower with medium rate was 43,48 kg/h; and blower with minimum rate was 52,63 kg/h. Keywords : blower, Soybean peeler, work capacity